Human resource transaction management system security optimize using multithreading with blowfish Algorithm - Krishna, Ashu; Rath, Satyajit; Kumar, Madhurendra (Gyan Management Journal, 2024)
Today HRMS (Human resource management system) application  around data transmitting from one place to another is challenging and  doing this with real-time data is even more difficult to service time  minimize and secure. In this paper using Blowfish algorithm with  multithreading technology we will solve the waiting time using dis tributed data streaming platform. This approach will become ideal to  daily life where each and every user get services in optimize way with  secure direction.
Keywords: HRMS; Blowfish algorithm; Data; Multithreading; management